2019
DOI: 10.1002/jcp.29288
|View full text |Cite
|
Sign up to set email alerts
|

LINC01559 accelerates pancreatic cancer cell proliferation and migration through YAP‐mediated pathway

Abstract: Pancreatic cancer (PC) is one of the top two most fatal cancers, with the poorest survival rate among all human malignancies. Increasing evidence suggests the involvement of long noncoding RNAs (lncRNAs) in the initiation and progression of various cancers. Herein, we investigated the role of lncRNA LINC01559 in PC.Several online databases indicated that LINC01559 was at a low expression in normal pancreatic tissues but was obviously upregulated in PAAD tissues. Further, our results showed that LINC01559 was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…LINC01559 has been identified as a potential non-invasive biomarker of renal cell carcinoma and is reported to accelerate pancreatic cancer cell proliferation and invasion through enhancing YAP activity, and UNC5B-AS1 is associated with tumourigenesis and metastasis of papillary thyroid cancer [21,23,34]. Our results suggest that LINC01559 and UNC5B-AS1 are novel regulators of aerobic glycolysis in PDAC.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…LINC01559 has been identified as a potential non-invasive biomarker of renal cell carcinoma and is reported to accelerate pancreatic cancer cell proliferation and invasion through enhancing YAP activity, and UNC5B-AS1 is associated with tumourigenesis and metastasis of papillary thyroid cancer [21,23,34]. Our results suggest that LINC01559 and UNC5B-AS1 are novel regulators of aerobic glycolysis in PDAC.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, FEZF1-AS1 has been demonstrated to promote the glycolytic phenotypes of colorectal cancer by regulating PKM2 signaling [18]. From the therapeutic point of view, we therefore verified the roles of LINC01559 and UNC5B-AS1, which have been implicated in several oncogenic processes but not involved in glycolysis [19][20][21][22][23]. Data from the TCGA + GTEx portal showed that LINC01559 and UNC5B-AS1 were highly expressed in the tumor tissues (n = 179) compared with normal pancreas samples (n = 171) ( Fig.…”
Section: Role Of Linc01559 and Unc5b-as1 In Pdac Glycolysismentioning
confidence: 53%
“…LINC02154 is risk factor for laryngeal cancer. LINC01559 accelerates pancreatic cancer cell proliferation and migration [28]. The co-expression network and function of these 10 lncRNAs were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This can in turn promote tumorigenesis [ 36 ]. LINC01559 was believed to play various roles in modulation of the YAP signaling pathways in the cytoplasm of pancreatic cancer cells [ 37 ]. In one mechanism, LINC01559 can act as a miRNA sponge of miR-607 to upregulate the expression of YAP1.…”
Section: Introductionmentioning
confidence: 99%
“…In one mechanism, LINC01559 can act as a miRNA sponge of miR-607 to upregulate the expression of YAP1. In an additional mechanism, LINC01559 can also directly bind to YAP1 and block its phosphorylation, thereby promoting its activation [ 37 ]. A similar role was also discovered for lncRNA THAP9 antisense RNA 1, which not only sponges miR-484, but also directly binds to YAP1 and inhibits phosphorylation-mediated inactivation by large tumor suppressor gene 1.…”
Section: Introductionmentioning
confidence: 99%